The effects of hydrocortisone on tight junction genes in an in vitro model of the human fallopian epithelial cells. (October 2018) - Zhaeentan, Shahrzad; Amjadi, Fatemeh Sadat; Zandie, Zahra; Joghataei, Mohammad Taghi; Bakhtiyari, Mehrdad; Aflatoonian, Reza
Abstract: The tight junction between epithelial cells helps making connections in the fallopian tube and contributes to successful fertilization. Breaking the tight junction complex induces various diseases such as the EP. Previous studies have shown that glucocorticoids are effective in repairing and maintaining intercellular tight junctions in epithelial cells of the fallopian tube, although their mechanism is still unknown. This research is a genomic study of hydrocortisone's effect on epithelial cells of the fallopian tube. Using the human fallopian tube, epithelial cell line (OE-E6/E7) was cultured in four concentrations of hydrocortisone (0 nM, 50 nM, 100 nM and 200 nM) for three durations (24 h, 48 h and 72 h). Glucocorticoids are effective on the expression of Zona occluding-1(ZO-1), C laudin 4, Claudin3, Desmoglein and E-cadherin genes involved in the tight junctions of the fallopian tube. The expression of all genes was up-regulated in the concentrations of 100 nM after 48 h treatment, as compared with the control (0 nM). However, their expression was down-regulated significantly after 72 h treatment (P < 0.05). The present study showed that treatment of epithelial cells of the fallopian tube with glucocorticoid increased the expression of genes involved in tight junctions, including claudin-3, claudin-4, E-cadherin, zona occludin-1 and Desmoglein-1. The obtained data suggests that a new mechanism is developed for glucocorticoid induction of tight junctions by increasing the expression of claudin-3, claudin-4, E-cadherin, zona occludin-1 and Desmoglein-1 genes.